Analisis Peraturan Perundang-Undangan Dalam Mendorong Kemandirian Ekonomi Usaha Mikro Kecil Menengah (UMKM) - Nabila, Sylvia; Ananda, Selva Putri; Alfariz, Muhammad Ridho; Satriana, Adam Ramadhan; Siswajanthy, Farahdinny (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This journal provides an analysis of regulations in an effort to encourage the economic independence of Micro, Small and Medium Enterprises (MSMEs). This journal was created with the aim of evaluating the effectiveness of implementing laws and regulations in national economic development to encourage the economic independence of MSMEs in Indonesia as well as legal protection related to MSMEs themselves. This journal will also discuss various laws and regulations related to MSMEs starting from the definition, objectives, juridical application and legal protection. The method used in writing this journal is a normative juridical approach which examines statutory regulations using primary legal materials, namely statutory regulations and secondary legal materials, namely journals. Keywords: Legal Regulation, MSMEs, Economic Law, Economic Independence, and National Development. Abstrak Jurnal ini memberikan analisis terhadap regulasi dalam upaya mendorong kemandirian ekonomi Usaha Mikro Kecil Menengah (UMKM). Jurnal ini dibuat bertujuan untuk mengevaluasi efektivitas penerapan peraturan perundang-undangan dalam pembangunan ekonomi nasional untuk mendorong kemandirian ekonomi UMKM di Indonesia serta perlindungan hukum terkait UMKM itu sendiri. Dalam jurnal ini juga akan membahas berbagai peraturan perundang-undangan terkait UMKM mulai dari definisi, tujuan, penerapan yuridis serta perlindungan hukumnya. Metode yang digunakan dalam penulisan jurnal ini ialah metode pendekatan yuridis normatif yang mengkaji peraturan perundang-undangan menggunakan bahan hukum primer yaitu peraturan perundang-undangan dan bahan hukum sekunder yaitu jurnal. Kata Kunci: Pengaturan Hukum, UMKM, Hukum Ekonomi, Kemandirian Ekonomi, dan Pembangunan Nasional